Hybrid soliton dynamics in liquid-core fibres - Mario Chemnitz (Nature Portfolio, 2017)
Here, Chemnitz et al. report experimental evidence for hybrid solitons – a type of solitary wave, which emerges as a result of a strong non-instantaneous nonlinear response in CS2-filled liquid-core optical fibres, demonstrating efficient soliton-driven supercontinuum generation.